Do people prefer cycling policy aiming at extending or saving lives? An experimental survey study. Issue 3 (September 2022) - Radun, Igor; Radun, Jenni; Kitti, Mitri; Kauppi, Heikki; Lajunen, Timo; Olivier, Jake
Highlights: We investigated the preference between transport policies aiming at extending vs. saving lives. We created a 2x2 experimental-survey scenario study. The parameters were realistic: 5 or 10 cyclist lives saved and 10:1 or 20:1 cost-to-benefit ratio of cycling. Our 2 × 2 experimental manipulation was not related to preference. More people preferred a policy aimed at saving lives (45.5% vs. 36%); 18.2% were undecided. Abstract: We investigated the preference between transport policies aiming at extending vs. saving lives. In a 2 × 2 experimental survey study participants randomly received one of four possible policy combinations. The saving lives policy included saving five (250 life-years saved) or ten (500 life-years saved) lives of cyclists who are about 30 years of age. The extending lives policy through the promotion of cycling and associated health benefits was set to extend lives by two ratios (10:1 or 20:1) in relation to life-years saved of the life-saving strategy. Participants were representative of Finnish-speaking residents older than 15 years (N = 1025). In total, 45.5% of the participants preferred a policy aimed at saving lives, 36% preferred an extending lives policy, and 18.2% were undecided. These figures remained essentially the same independent of the benefit-to-cost ratio of cycling (in terms of saved life years) and whether the saving life policy meant saving five or ten lives. Women and the elderly preferred a policy aimed at saving lives, while cyclists preferred an extending lives policy. The results are discussed in the context of Vision Zero and a new transport paradigm called Vision Plus.